Problems of Criminalistic Characteristics of Fraud in the Field of Real Estate - KURANBEK, Zhebegen A. (Journal of Advanced Research in Law and Economics, 2019)
Property is considered as one of the important objects protected by law. At the same time, the development different areas of financial and economic activity simultaneously create new types of criminal activity. Fraud, as one of them, requires careful research by scientists and practitioners, which explains the relevance of this study. The paper aims to consider the problems of criminalistic characteristics of fraud in the field of real estate. The author comes to the conclusion that fraud is a collective term, which unites a wide group of socially dangerous encroachments. Despite this, the analysis of the methods of fraud allowed to highlight some general patterns of the formation of traces of a crime.